Psychiatric Nurses’ Roles in Preventing Facebook Addiction in Adolescents - ทองประดับ, จุฑามาศ (Journal of Thailand Nursing and Midwifery Council, 2020)
Abstract: Facebook addiction is found in an increasing number of adolescents. However,no serious attention has been paid to this addiction. Unaware of the situation, healthcare personnel may assume that this addiction is a normal adolescent behaviour that is likely to stop when they grow older. Such an assumption could result in inappropriate care given to adolescent Facebook addicts and escalation of the severity of their addiction, a situation that may affect their studies, physical and mental health, and performance of their social roles. Therefore, psychiatric nurses play an important role in preventing Facebook addiction in adolescents, especially those with a high addiction risk. It is suggested that nurses cooperate with parents and teachers to provide proper education for adolescents. This article discusses Facebook addiction in terms of: its defnition; its mechanisms; its effects; its evaluation; and roles of psychiatric nurses in preventing it. It is expected that this article will provide psychiatric nurses with basic knowledge of monitoring, preventing, and reducing risks of Facebook addiction